The effects of using system dynamics-based decision support models: testing policy-makers' boundaries in a complex situation. Issue 1 (2nd January 2017) - Bérard, Céline; Cloutier, L. Martin; Cassivi, Luc
Abstract: Systems thinking and computer-based modelling systems are widely recognised as effective for solving complex problems, particularly for the potential changes they can trigger in decision-makers' perception of where problems' boundaries lie. Surprisingly, few studies have analysed their empirical effects on decision-making. This paper explores the effects of the use of a system dynamics-based decision support system (DSS) by decision-makers, focusing on boundary judgements, which indicate what issues and stakeholders are to be included in the decision analysis. The data were obtained from an experiment with 40 policy-makers, using a simulated case approach that focused on the complex biotechnology intellectual property system. They suggest that the use of such a DSS favours both the analysis of a greater range of perspectives and broader stakeholder participation, but does not strengthen either interdisciplinary integration or depth of stakeholder participation.